Quality of consent form completion in orthopaedics: are we just going through the motions?. Issue 7 (6th July 2010) - Jeyaseelan, Luckshmana; Ward, Jonathan; Papanna, Madhavan; Sundararajan, Sabapathy
Abstract : Consent plays a vital role in every aspect of medicine and surgery, facilitating the patient in making informed decisions about their treatment. The recently published Reference Guide to Consent, by the Department of Health (DH), notes that, although not a legal requirement, the completion of consent forms is good practice, particularly in interventions such as surgery. In addition, the Parliamentary and Health Service Ombudsman noted that a significant number of complaints about consent involved the complainant feeling that they did not fully understand what was going to happen. It was often found that there was no documentation to clarify what the patient was told, when and by whom. We have performed an audit of 71 randomly selected consent forms, elective and trauma cases within our district general hospital orthopaedics department. Our data demonstrate that a significant number of consent forms were incorrectly or insufficiently completed. This could not only leave the patient confused about their procedure but also leaves the doctor open to litigation, with little in the way of documentation support. Minor changes in consenting methods and more precise documentation could significantly improve patient experience and satisfaction.